Do Women Directors Constraint Accrual Management? Malaysian Evidence - Abdullah , Shamsul Nahar (2012)
Women are found to be more risk averse than men (Fehr-Duda, 2006; Watson & McNaughton, 2007; Eckel & Grossman, 2008). Women are also different from men in their leadership styles and attitudes towards ethics and risks (Gul, Srinidhi & Tsui, 2007). These differences suggest that the presence of women is capable of reducing accrual management. Our empirical results show that the presence of women on the board and audit committee is not associated with accrual management. Hence, women do not appear to perform the accounting oversight role well.